Clinicopathological Correlation of Non-Alcoholic Fatty Liver Disease with Metabolic Syndrome Components in Tertiary Care Patients - Sheema Khan, Aisha Asim, Muhammad Azhar Khan, Syed Hasnain Abbas, Mahwash Mansoor, Ikram Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is increasingly recognized as the hepatic manifestation of metabolic syndrome and is strongly associated with central obesity, dyslipidemia, hypertension, and impaired glucose metabolism. The coexistence of these metabolic risk factors accelerates hepatic injury and progression to non-alcoholic steatohepatitis, fibrosis, and cirrhosis. Limited data exist from Pakistan regarding the clinicopathological correlation of NAFLD with metabolic syndrome components in tertiary care settings. Objective: To evaluate the clinicopathological correlation of NAFLD with metabolic syndrome components in patients presenting to tertiary care hospitals. Methods: This cross-sectional observational study was conducted at Khyber Teaching Hospital, Peshawar, and Sughra Shafi Medical Complex, Narowal, Pakistan, from January 2022 to March 2023. A total of 100 adult patients with ultrasonographically confirmed NAFLD were included. Clinical assessment, anthropometric measurements, fasting blood sugar, lipid profile, and liver function tests were performed. The presence of metabolic syndrome was defined using NCEP-ATP III criteria. Patients with persistent elevation of transaminases underwent liver biopsy, and histopathological grading was assessed using the NAFLD Activity Score. Results: Sixty-eight percent of patients met the criteria for metabolic syndrome. Central obesity (71%), impaired fasting glucose (58%), and low HDL cholesterol (60%) were the most common abnormalities. Patients with metabolic syndrome exhibited significantly higher fasting glucose, triglycerides, and ALT levels compared to those without. Histopathological evaluation revealed that metabolic syndrome was associated with higher grades of steatosis, lobular inflammation, ballooning, and fibrosis (p<0.05). Conclusion: NAFLD is strongly correlated with metabolic syndrome, and increasing metabolic burden is associated with more severe biochemical and histological changes. Early screening and management of metabolic risk factors are vital for preventing disease progression. Keywords: Non-alcoholic fatty liver disease, metabolic syndrome, hepatic steatosis, histopathology, obesity, insulin resistance.